2016
DOI: 10.5380/abclima.v18i0.38840
|View full text |Cite
|
Sign up to set email alerts
|

Identificação De Variabilidades E Tendências Interanuais Em Medidas Hidro-Climáticas Na Região Hidrográfica Do Tocantins-Araguaia, Brasil (Identification of Variability and Inter-Annual Trends in Hydro-Climate Measures at the Tocantins River Basin District-Araguaia, Brazil)

Abstract: Mudanças promovidas pelo clima e por ações antrópicas podem gerar significativos impactos sobre o regime hidrológico de uma bacia hidrográfica. Neste estudo, avaliou-se a ocorrência de tendências em séries temporais anuais de precipitação pluviométrica, temperaturas mínima, média e máxima e de vazões em rios, registradas em localidades pertencentes à bacia hidrográfica do Tocantins–Araguaia, no nordeste do Brasil. Procurou-se identificar, por meio de testes estatísticos, eventuais pontos de mudança no comporta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Previous studies in eastern Brazilian Legal Amazon did not observe statistically significant trends in precipitation (Souza et al, 2017;Penereiro et al, 2016) or temperature (Penereiro et al, 2016). However, Penereiro et al (2016) found a positive trend in the Itacaiúnas water level between the 1970s and the 2010s, with a turning point in 1984. Additionally, the authors observed positive trends in some gauge stations at the upper Araguaia River basin but negative trends in some gauges in the middle of the Tocantins River basin.…”
Section: Study Areamentioning
confidence: 69%
“…Previous studies in eastern Brazilian Legal Amazon did not observe statistically significant trends in precipitation (Souza et al, 2017;Penereiro et al, 2016) or temperature (Penereiro et al, 2016). However, Penereiro et al (2016) found a positive trend in the Itacaiúnas water level between the 1970s and the 2010s, with a turning point in 1984. Additionally, the authors observed positive trends in some gauge stations at the upper Araguaia River basin but negative trends in some gauges in the middle of the Tocantins River basin.…”
Section: Study Areamentioning
confidence: 69%
“…As described by Ferreira 2011, andPenereiro et al 2016, the Pettitt's test is based on the null hypothesis H0: the hydrological series Xn shows no abrupt change, and its application is not conditioned by an a priori specification of the instant the change occurs (if it occurs). The statistic , counts the number of times a member of the first sample is larger than a member of the second sample, as defined by the following equation:…”
Section: Pettitt's Testmentioning
confidence: 99%
“…The intersection of M-K curves ( ) and ( ) with the confidence intervals happened in 1997, while PETT curve ( ), shown in the top graphic of the same figure, crossed the two confidence levels with the maximum inferred in 1995. However, according to Penereiro, Martins, and Beretta (2016), the PETT test is a statistical method focused on detecting abrupt changes in historical series. Thus, even though these observed years are delayed in two years of each other, we decided to confirm that there is a negative trend in this series starting in 1995, considering the date inferred by PETT test.…”
Section: Resultsmentioning
confidence: 99%